Analysis Of Antioxidant Content Of Anthocyanin In The Lobi-Lobi Fruit (Flacourtian Inermis) And Jamblang Fruit (Syzygium Cumini L Skeel) Using The Dpph Method With Spectrophotometry - Fazrul M. Yasin; Zulkifli Zam Zam; Khusna Arif Rakhman (Universitas Airlangga, 2022)
This study aimed to determine the total anthocyanin content and IC50 value) of antioxidants from the ethanol extract of Lobi-lobi (Flacourtia Inermisand Jamblang (Syzygium Cuini L Skeel) fruit which were analyzed using the DPPH method. by UV-Vis spectrophotometry. The research was conducted at the Environmental Laboratory of the Faculty of Teacher Training and Education, Khairun University. The results showed that the anthocyanin content and antioxidant activity of the lobi and jamblang fruit were analyzed using the Differences in pH and DPPH methods. For lobbies anthocyanin levels are 17.99 mg/L and 4.62 mg/L. Meanwhile, for IC50 antioxidants from fruit lobbies, 50.01 g/L was obtained, for jamblang it was 91,113 g/L.